THE EFFECT OF INQUIRY METHOD ON STUDENTS’ READING COMPREHENSION OF ANALYTICAL EXPOSITION TEXT (A STUDY AT THE ELEVENT AL- ABRAAR SIONDOP JULU ANGKOLA SELATAN IN 2020/2021 ACADEMIC YEAR) - srimaharani tanjung (JURNAL LINER (Language Intelligence and Educational Research), 2022)
Abstract :The purpose of this research to know 1) the application of inquiry method on students’ reading comprehension of analytical exposition text , 2) The students’ reading comprehension of analytical exposition text before and after using inquiry method, 3) whether there is any significant effect of inquiry method on students’ reading comprehension of analytical exposition text. This research used experimental method with the pre-experimental design by using one-group pretest and posttest design. The sample of this research is 22 students of class XI-C by using purposive sampling. In collecting the data, the researcher used observation sheet and test. The result of the research are 1) application of inquiry method was 3.3 (very good category), 2) the average score of students’ reading comprehension of analytical exposition text before and after using inquiry method is 43.36 (fail category) and is 72.95 ( good category), 3) The results of the analysis show that ttest is greater than ttable.. (7.77 > 2.08). So, the hypothesis is accepted. It means that there is any significant effect of inquiry method on reading comprehension of analytical exposition text for class XI- C students’ of MAS AL- Abraar Siondop Julu Angkola Selatan. Key Word: Reading Comprehension, Analytical Exposition Text, Inquiry Method